2016
DOI: 10.1182/blood.v128.22.181.181
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab for Treatment of Relapsed/Refractory Mycosis Fungoides and Sezary Syndrome: Clinical Efficacy in a Citn Multicenter Phase 2 Study

Abstract: Background:PD-1 and PD-L1/PD-L2 are expressed by malignant T-cells in mycosis fungoides (MF) and Sézary syndrome (SS). PD-1 is additionally expressed by tumor-infiltrating cytotoxic T-cells and PD-L1 is expressed by macrophages and other stromal components of the tumor microenvironment in these diseases. Moreover, reports of 9p24.1/PD-L2 translocation and CTLA4-CD28 fusion events in MF/SS support a genomic basis for immune evasion. Here, we explore the clinical activity of pembrolizumab, an immune checkpoint i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 0 publications
0
41
0
2
Order By: Relevance
“…Responses correlated with a high PD‐1 level, which may be upregulated by the EBV viral proteins. Encouraging results were also seen with pembrolizumab in patients with R/R cutaneous T‐cell lymphoma with response rates of 38% seen in a small phase 2 trial reported from Stanford . Nivolumab has demonstrated efficacy in a phase 1 study that included five patients with PTCL, but the ORR was only 13% .…”
Section: Specific Targeted Therapies and Clinical Implicationsmentioning
confidence: 96%
“…Responses correlated with a high PD‐1 level, which may be upregulated by the EBV viral proteins. Encouraging results were also seen with pembrolizumab in patients with R/R cutaneous T‐cell lymphoma with response rates of 38% seen in a small phase 2 trial reported from Stanford . Nivolumab has demonstrated efficacy in a phase 1 study that included five patients with PTCL, but the ORR was only 13% .…”
Section: Specific Targeted Therapies and Clinical Implicationsmentioning
confidence: 96%
“…The 1‐year median PFS was not reached and the toxicity was similar to those in previous studies of pembrolizumab. Specific immune‐mediated AEs included a skin flare reaction that occurred exclusively in patients with SS (40%) and one patient experienced grade 3 diarrhoea secondary to steroid‐refractory duodenitis …”
Section: Lymphoid Malignanciesmentioning
confidence: 99%
“…Development of immune checkpoint inhibitors is an important advance in the treatment of human cancers, and this approach has shown significant promise for treatment of a variety of HM. Novel drug combinations, identification of targets in the immune TME, and clinical trials of agents that modulate immune checkpoints beyond CTLA-4 and PD-1/PD-L1 are ongoing with the aim to expand the utility of immune-based approaches for treatment of all patients with lymphoid, plasma cell and *, mechanism of action unclear after uncertainty as pidilizumab does not bind PD-1 (48). N/A, not applicable.…”
Section: Discussionmentioning
confidence: 99%